Short circuit fault analysis and solution research of equipment electric gas cabinet under conductive dust pollution environment. Issue 1 (February 2021) - Mei, Ke; Li, Xiaofei; Gu, Chao
Abstract: The production of conductive dust not only pollute the environment, harm people's health, but also bring great harm to the safe operation of electrical equipment. Such as shorting electrical equipment, electrical switch according to touch bad, poor ventilation, etc., it is easy to cause equipment electrical cabinets failure problems, in order to strengthen the reliability of enterprise production, for the timely and effective maintenance of the equipment failure, and take effective measures to guarantee with the safe operation of the equipment electrical cabinets in conductive dust environment. A great deal of work has been done in this paper to prevent the harm of dust to the electrical equipment and remarkable results have been obtained.